2011
DOI: 10.1177/1470320311408750
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exercise attenuates blood pressure responsiveness and modulates kidney angiotensin II signalling and urinary sodium excretion in SHR

Abstract: Observations have been made regarding the effects of long-term exercise training on blood pressure, renal sodium handling and renal renin-angiotensin-aldosterone (RAS) intracellular pathways in conscious, trained Okamoto-Aoki spontaneously hypertensive rats (SHR) and Wistar Kyoto (WKy) normotensive rats, compared with appropriate agematched sedentary SHR and WKy. To evaluate the influence of exercise training on renal function and RAS, receptors and intracellular angiotensin II (AngII) pathway compounds were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
0
29
1
3
Order By: Relevance
“…Because role of AngII is well established in regulation of renal excretion of water and electrolyte, exercise-induced increase in urinary sodium excretion could also attribute to pressure-lowering effects of exercise. For instance, Ciampone et al (2011) have recently reported an association between reduced BP, increased natriuresis, and improvement in renal RAS components[8]. It is also important to discuss that adipocytes are known to play an important role in cytokine production and a recent study reported increased ACE expression by adipocyte-derived lipid mediators in macrophages [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because role of AngII is well established in regulation of renal excretion of water and electrolyte, exercise-induced increase in urinary sodium excretion could also attribute to pressure-lowering effects of exercise. For instance, Ciampone et al (2011) have recently reported an association between reduced BP, increased natriuresis, and improvement in renal RAS components[8]. It is also important to discuss that adipocytes are known to play an important role in cytokine production and a recent study reported increased ACE expression by adipocyte-derived lipid mediators in macrophages [32].…”
Section: Discussionmentioning
confidence: 99%
“…Inc, MA, USA), respectively. Thereafter, animals were anaesthetized with ketamine and xylazine injected intraperitoneally and sacrificed by cardiac puncture; urine and plasma samples were stored for analysis [3,4,6,7,29,30]. …”
Section: Methodsmentioning
confidence: 99%
“…Fractional sodium excretion (FE Na ) was calculated as C Na /C Cr ×100, where C Na is sodium clearance. Fractional proximal (FEP Na ) and post-proximal (FEPP Na ) sodium excretion were calculated as C Li /C Cr × 100 and C Na /C Li × 100, respectively [3,4,6,7,29,30]. Data obtained over time were analyzed using two-way ANOVA or nonparametric analysis using the Kruskal–Wallis test.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in rodents find chronic exercise to inhibit tissue RAS activation in the brain (58) (reduced local ACE and AT 1 R), heart (59, 60) (reduced local ACE and ANG II), and kidney (reduced local AT 1 R) (61). These findings suggest that down-regulation of tissue RAS may partly mediate the beneficial effects related to frequent exercise.…”
Section: Tissue Ras Regulationmentioning
confidence: 99%